Navigating Organizational Challenges And Tasks In The Digital Transformation Era - Sunarti, Sri; Sandy, Denti Septi Aria; Subandi, Subandi; Syarifudin, Encep; Makbuloh, Deden (Tatar Pasundan: Jurnal Diklat Keagamaan, 2024)
This article discusses the main challenges and tasks of organizations in the contemporary era which is influenced by technological advances, globalization and shifting social values. Modern organizations are faced with rapid change that is driving the need to adapt, both in adopting digital technologies such as AI and IoT and in responding to increasingly high consumer expectations for sustainability and social responsibility. Key challenges include globalization, digital transformation, sustainability, diversity, as well as the need for innovation and resilience in the face of crises. Organizations need to develop innovation strategies, risk management, and build an inclusive work culture to remain relevant and competitive. Data collection techniques were carried out using literature studies from various articles, books and research results. In conclusion, the success of an organization in the modern era depends on its ability to adapt, manage risk, and implement sustainability in business operations Keywords: challenge; contemporary; digital transformation; organization; task